Essentials of performance analysis in sport - Hughes, M.; Franks, Ian M. (Routledge, Taylor & Francis Group, 2015)
This second edition includes three completely new chapters covering the key emerging topics of dynamic systems, momentum and performance profiling, as well as updated coverage of core topics in the performance analysis curriculum such as designing notation systems, analysing performance data, qualitative analysis of technique, time-motion analysis, probability, using feedback technologies, performance analysis and coaching.